DIGITALIZATION AS A FACTOR OF THE DEVELOPMENT OF INNOVATIVE THINKING OF HIGHER EDUCATION STUDENTS - TSIUNIAK, Oksana; HOTSANIUK Tetіana (Mountain School of Ukrainian Carpaty, 2025)
The article provides a comprehensive analysis of the impact of digitalization on the development of innovative thinking among higher education students. The essence of the terms «digitalization» and «innovative thinking» is revealed. Normative and legal documents on the development of Ukraine's digital economy and society are analyzed, emphasizing the necessity of integrating digital tools into education to promote the development of students innovative thinking. Challenges related to the influence of digitalization on the development of innovative thinking of higher education students are outlined, the solution of which requires an integrated approach, including enhancing digital literacy, modernizing educational programs in higher education institutions, ensuring equal access to technology and developing ethical and social skills in the digital environment. The personal qualities of higher education students associated with the development of innovative thinking are characterized: generating new and unconventional ideas; rejection of stereotypes and templates; desire to learn new things; ability to use the experience of others, if necessary; ability to analyze, synthesize and generalize; originality of views and flexibility of thinking; ability to creatively solve professional problems; focus on gaining practical experience; search for different ways to implement professional ideas. An empirical study of the development of innovative thinking among higher education students was conducted. The results of the survey indicate that digital technologies, including educational platforms, online libraries, and knowledge- sharing programs, significantly enhance the learning process, promote innovative thinking, and contribute to the formation of students professional competencies an essential component of their professional readiness for the digital transformation of education. It is concluded that digitalization is an important factor in the development of innovative thinking of higher education students, and digital technologies are a powerful tool for organizing the educational process in the context of society informatization and facilitate the assimilation of educational material, promote cooperation, self-realization and professional development of future professionals.